Boosting Antitumor Response by Costimulatory Strategies Driven to 4-1BB and OX40 T-cell Receptors - Mascarelli, Daniele E.; Rosa, Rhubia S. M.; Toscaro, Jessica M.; Semionatto, Isadora F.; Ruas, Luciana P.; Fogagnolo, Carolinne T.; Lima, Gabriel C.; Bajgelman, Marcio C. (Frontiers in Cell and Developmental Biology, 2021)
Immunotherapy explores several strategies to enhance the host immune system’s ability to detect and eliminate cancer cells. The use of antibodies that block immunological checkpoints, such as anti–programed death 1/programed death 1 ligand and cytotoxic T-lymphocyte–associated protein 4, is widely recognized to generate a long-lasting antitumor immune response in several types of cancer. Evidence indicates that the elimination of tumors by T cells is the key for tumor control. It is well known that costimulatory and coinhibitory pathways are critical regulators in the activation of T cells. Besides blocking checkpoints inhibitors, the agonistic signaling on costimulatory molecules also plays an important role in T-cell activation and antitumor response. Therefore, molecules driven to costimulatory pathways constitute promising targets in cancer therapy. The costimulation of tumor necrosis factor superfamily receptors on lymphocytes surface may transduce signals that control the survival, proliferation, differentiation, and effector functions of these immune cells. Among the members of the tumor necrosis factor receptor superfamily, there are 4-1BB and OX40. Several clinical studies have been carried out targeting these molecules, with agonist monoclonal antibodies, and preclinical studies exploring their ligands and other experimental approaches. In this review, we discuss functional aspects of 4-1BB and OX40 costimulation, as well as the progress of its application in immunotherapies.